Functional Analysis of Narrative Texts in Elementary School Textbook Fly with English - Jati, Ambar; , Dra. Malikatul Laila, M.Hum (2017)
This study is an analysis of narrative texts in Elementary School textbook "Fly with English" based on lexico-grammar and context in the framework of Systemic Functional Linguistics (SFL). This study is also expected to give the pedagogical implication based on the context of teaching and learning process. The aims of this research are (1) finding out the types of processes, participants, and circumstances, (2) realizing the ideational meaning, and (3) explaining the pedagogical implication of narrative text analysis. This research uses descriptive qualitative type of study in investigating the problem. In the technique of collecting data, the writer uses observation and documentation. The writer finds 95 clauses in narrative text. In analyzing the data, the writer uses lexico-grammar of SFL framework to answer the first problem. Moreover, the writer refers to context of SFL framework to answer the second problem, and the writer also uses context of teaching and learning to answer the third problem. Based on the result, there are six types of processes in the narrative text, those are: (1) material process (40%), (2) mental process (23,1%), (3) relational process (20%), (4) verbal and behavioral process (7,4%), and (5) existential process (2,1%). Material process is the dominant process. The writer also finds fifteen types of the participants, namely actor, goal, senser, phenomenon, sayer, verbiage, carrier, attribute, token, value, receiver, client, recipient, behaver, and existent. The most dominant participant is material's participants (35,7%). It indicates that the author often employs the process of happening or doing in order to reveal the idea or experience that are appropriate with the learner's level. Moreover, the writer finds six types of circumstances, that are, location, matter, manner, accompaniment, cause, and extent. The result shows that the most dominant circumstance is circumstance of location (46,1%). The author who employs many circumstances of location will give clear setting of the narrative text, so the reader will understand the plot of story. The pedagogical implication of studying Systemic Functional Linguistics (SFL) in narrative text is to give the insight of the teacher about SFL genre pedagogy in teaching and learning process. In functional grammar, teacher can teach the language features in different ways, such as by introducing the terms of processes, participants, and circumstances that contain in the narrative text clauses. Keyword: SFL, ideational meaning, narrative text, process, and circumstance.